Infidel - Hirsi Ali, Ayaan (New York Free Press, 2008)
Ayaan Hirsi Ali is one of today's most admired and controversial political figures. She burst into international headlines following the murder of Theo van Gogh by an Islamist who threatened she would be next. An international bestseller, her life story INFIDEL shows the coming of age of this elegant, distinguished -- and sometimes reviled -- political superstar and champion of free speech. Ultimately a celebration of triumph over adversity, Hirsi Ali's story tells how a bright, curious, dutiful little girl evolves into a pioneering freedom fighter. As Western governments struggle to balance democratic ideals with religious pressures, no other book could be more timely, or more significant.
Keywords: Hirsi Ali, Ayaan, 1969-